Regression Test Suite Reduction (International Journal of Advanced Research in Science, Management and Technology, 2015)
Regression testing is a software maintenance activity. Regression testing is the process of testing changes to computer programs to make sure that the older programming still works with the new adjustments. Test suites tend to growing size as software evolve, often making it too costly to execute entire test suite sin the given time and constraints. Hence it becomes an essential to minimize the test suite and choose a subset of test cases from test suite which will be execute din least time and has the capability to cover all the errors, Thus it is advisable to choose certain test cases and prioritized them with the objective to under size the whole test suite dimension. A number of different approaches have been studied to maximize the value of the accrued test suite: minimization, selection and prioritization. Test suite minimization seeks to eliminate redundant test cases in order to reduce the number of tests to run. Test case selection seeks to identify the test cases that a irrelevant to some set of recent changes. Test case prioritization seeks to order test cases in such a way that early fault detection is maximized.
Keywords: Regression Testing, Test Case Selection, Set Theory